Evidence for a quadruplex structure in the polymorphic hs1.2 enhancer of the immunoglobulin heavy chain 3' regulatory regions and its conservation in mammals. Issue 11 (November 2016) - Sette, Marco; D'Addabbo, Pietro; Kelly, Geoffrey; Cicconi, Alessandro; Micheli, Emanuela; Cacchione, Stefano; Poma, Anna; Gargioli, Cesare; Giambra, Vincenzo; Frezza, Domenico
ABSTRACT: Regulatory regions in the genome can act through a variety of mechanisms that range from the occurrence of histone modifications to the presence of protein‐binding loci for self‐annealing sequences. The final result is often the induction of a conformational change of the DNA double helix, which alters the accessibility of a region to transcription factors and consequently gene expression. A ∼300 kb regulatory region on chromosome 14 at the 3' end (3'RR) of immunoglobulin (Ig) heavy‐chain genes shows very peculiar features, conserved in mammals, including enhancers and transcription factor binding sites. In primates, the 3'RR is present in two copies, both having a central enhancer named hs1.2. We previously demonstrated the association between different hs1.2 alleles and Ig plasma levels in immunopathology. Here, we present the analysis of a putative G‐quadruplex structure (tetraplex) consensus site embedded in a variable number tandem repeat (one to four copies) of hs1.2 that is a distinctive element among the enhancer alleles, and an investigation of its three‐dimensional structure using bioinformatics and spectroscopic approaches. We suggest that both the role of the enhancer and the alternative effect of the hs1.2 alleles may be achieved through their peculiar three‐dimensional‐conformational rearrangement. © 2016 Wiley Periodicals, Inc. Biopolymers 105: 768–778, 2016.